A methodology for incorporating quality assurance practices during software development life cycle - Laaraib, Eraj; Ahmed Maher, Zulfikar; Ali Solangi, Zulfiqar; Koondhar, Muhammad Yaqoob; Memon, Mukhtiar; Depar, MansoorHyder; Shah, Asadullah (World Academy of Research in Science and Engineering, 2021)
The aim of quality assurance in software development is to ensure that a software product meets its practical business specifications and quality requirements. A comprehensive overview of different software quality requirement and quality assurance practices have been performed to find out the most appropriate software quality assurance practices at different stages of the software development life cycle (SDLC). A methodology along with its implementation during SDLC has been proposed in this research paper. The proposed methodology will help software development teams to achieve quality assurance goals during software development.